2014
DOI: 10.1371/journal.pone.0086162
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Instability Persists in Non-Neoplastic Urothelial Cells from Patients with a History of Urothelial Cell Carcinoma

Abstract: Bladder cancer is one of the most common genitourinary neoplasms in industrialized countries. Multifocality and high recurrence rates are prominent clinical features of this disease and contribute to its high morbidity. Therefore, more sensitive and less invasive techniques could help identify individuals with asymptomatic disease. In this context, we used the micronucleus assay to evaluate whether cytogenetic alterations could be used as biomarkers for monitoring patients with a history of urothelial cell car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…By contrast, slides from the control group did not contain MN 36 . Based on our findings and those of these aforementioned studies, it can be concluded that subjects who are at high risk for UCC, who have UCC, or who have a history of UCC harbour and accumulate genetically unstable cells in the bladder urothelium, which may represent early precursors of new UCC or subclones from previous UCC 35 . Lastly, it can be deduced that these changes can be readily detected via an MN assay performed on urine.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…By contrast, slides from the control group did not contain MN 36 . Based on our findings and those of these aforementioned studies, it can be concluded that subjects who are at high risk for UCC, who have UCC, or who have a history of UCC harbour and accumulate genetically unstable cells in the bladder urothelium, which may represent early precursors of new UCC or subclones from previous UCC 35 . Lastly, it can be deduced that these changes can be readily detected via an MN assay performed on urine.…”
Section: Discussionsupporting
confidence: 69%
“…This result agrees with a previous study that phenotypically profiled urothelial cells in patients with a prior history of UCC 34 . Similarly, the results of a separate previous study indicated that the MN frequency in urothelial cells from bladder washings of patients with a history of UCC was higher than that of the control group 35 . Furthermore, in a retrospective study of urine samples, slides that had been identified as atypical urothelial cells and subsequently diagnosed as UCC positive were found to be positive for MN.…”
Section: Discussionmentioning
confidence: 57%
“…To our knowledge, only few studies investigated if the MN assay could be applied as a diagnostic tool to identify individuals who have BC (Arora et al , 2010; Sharma et al , 2012; de Castro Marcondes et al , 2014). The currently available data suggested that MN assays in UDC may be potentially a suitable diagnostic tool for detection of BC and for the surveillance of the patients (Nersesyan et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Micronucleated cell indexes may reflect genetic damage (de Castro Marcondes et al 2014). The detection of an elevated frequency of micronuclei in a given population indicates increased risk of cancer.…”
Section: Discussionmentioning
confidence: 99%